The effects of marketing stimuli factors on consumers’ perceived value and purchase of organic food in Malaysia - Song, Bee Lian; Meysam Safari,; Shaheen Mansori, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this study is to examine the effects of marketing stimuli factors on consumers’ perceived value and subsequently on their actual purchase of organic food in Malaysia. Five key marketing stimuli variables were examined in this study, and they were product attributes, price, availability, sales promotion and marketing communications.This paper presents the results of a survey conducted on a sampleof 430 organic food consumers in Malaysia. The structural equation modelling was used for data analysis and six hypotheses were tested. The results revealed that product attributes, availability and marketing communication have significantly influence dconsumers’ perceived value of organic food. Subsequently, consumers’ perceived value is positively correlated to the actual purchase of organic food. There was no significant effect of price and sales promotion on consumers’ perceived value of organic food.Based on the findings, the marketing stimuli strategies should be focused on providing superior value to consumers in the aspects of nutritional value, long term health benefits, environment friendliness, social status symbol and easy accessibility to increase consumers’ purchase of organic foods.